2000
DOI: 10.1046/j.1464-410x.2000.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing lithoclast with an electrokinetic lithotripter in the management of ureteric stones

Abstract: Objective To compare two in situ ballistic lithotripters, the lithoclast and the electrokinetic lithotripter (EKL), both of which can be used through the newer smallbore ureteroscopes, for their ease of use, robustness, fragmentation time, adequacy of fragmentation and stone-free rate. Patients and methods Forty-six consecutive patients with ureteric stones refractory to treatment by extracorporeal shock wave lithotripsy were randomized to undergo fragmentation using the lithoclast (23 patients) or the EKL (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…In fact, use of grasping forceps allowed the procedure to be equally effective, when complete fragmentation had not been achieved, even though it prolonged operating times in such cases. In our experience, as already noted by Menezes et al [11], the SLC handset is more comfortable, since it is lightweight and very easy to hold in one hand. We do not usually use the provided holder that attaches to the ureteroscope to prevent the probe from bending.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In fact, use of grasping forceps allowed the procedure to be equally effective, when complete fragmentation had not been achieved, even though it prolonged operating times in such cases. In our experience, as already noted by Menezes et al [11], the SLC handset is more comfortable, since it is lightweight and very easy to hold in one hand. We do not usually use the provided holder that attaches to the ureteroscope to prevent the probe from bending.…”
Section: Discussionsupporting
confidence: 76%
“…In a randomized trial, Menezes et al [11] found no significant differences in the stone-free rate, procedure duration, fragmentation time, proximal stone migration rate and equipment failure in these in situ ballistic lithotripters. In the same paper they made some practical recommendations for sterilizing the handset of both lithotripters and commented on their weight and shape, concluding that simplicity of use and ease of repair make the SLC an attractive choice.…”
Section: Discussionmentioning
confidence: 97%
“…Advantage of pneumatic lithotripter when compared to other lithotriptors is its lower risk of perforating ureter and no thermal damage (13). Only concern with pneumatic lithotripter is stone migration, that ranges between 1.6% and 17.3% particularly with upper ureteral calculus (14, 15). …”
Section: Discussionmentioning
confidence: 99%
“…[28] In a study performed by Santa-Cruz et al [29] on experimental animal models, the authors reported that after directly sending shock waves from a pneumatic lithotriptor on ureteral wall for 6 minutes, ureteral wall perforation did not occur.In the literature rates of stone migration with pneumatic lithotriptor range between 1.6, and 17.3%, which is more frequently seen with proximal ureteral stones. [6,30,31] Nowadays, ureteroscopy has become the first alternative in most centers with a success rate approaching to 100 percent. EAU indicated a success rate over 90% with PL in the endoscopic treatment of ureteral stones.…”
Section: Discussionmentioning
confidence: 99%